2011
DOI: 10.19030/jber.v7i9.2336
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability And Infrastructure Resource Allocation

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt;"><span style="font-size: 10pt;"><span style="font-family: Times New Roman;">Sustainability implies using, developing and protecting resources in such a manner that enables society to meet current needs and provides that future generations will be able to meet their needs, from the joint perspective of economic, environmental and social objectives. Sustainable resource use implies a concern for intergenerational equity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A correct allocation of resources is needed to ensure sustainable management. The ultimate goal would be to simultaneously support economic growth, environmental protection, and social equity . However, these aspects represent a great challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A correct allocation of resources is needed to ensure sustainable management. The ultimate goal would be to simultaneously support economic growth, environmental protection, and social equity . However, these aspects represent a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal would be to simultaneously support economic growth, environmental protection, and social equity. 25 However, these aspects represent a great challenge. In this regard, an economic approach to involve sustainability in process integration projects has been reported by El-Halwagi.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In traffic control, in some cases it is observed that when efficiency is selected as the single most important measure, the impacts are not consistent with either environmental or social sustainable transportation principles [9]. Therefore, equity issues should be taken into account in traffic management and control.…”
Section: Introductionmentioning
confidence: 99%